Perancangan User Experiance Website Travel Mabruro Menggunakan Pendekatan Human-Centered Design - Safira Nur Rahmah; Hanifah Muslimah Az-Zahra; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT Mabruro Tour and Travel is a company that focuses on organizing Hajj and Umrah. However because of the COVID-19 pandemic, Travel Mabruro need online services in managing registration and administration to reduce physical contact, for this reason Travel Mabruro utilizes a previously owned website to add these services. In order to add these services to run according to the needs and goals, a website user experience design is carried out which began with a business process analysis then the results of the analysis are used as references in interface design. To produce services that are suitable with the needs, the Human-Centered Design (HCD) approach is used. Focusing on producing a service system that can be useful and beneficial by involving humans (in this case users and stakeholder) which aims to meet the needs and satisfaction of users and also achieve organizational goals that are previously planned. It consists of several stages, the first stage is to specify the context of use and user needs which are obtained by conducting interview with stakeholders (Travel Mabruro) and user who will use these services, then planning the design solution by making wireframe, screenflow and high-fidelity prototype which will be the final result of the Travel Mabruro interface. After that, the result of design solution will be evaluated using the User Experience Questionnaire (UEQ) method. The evaluation results obtained a positive value on each UEQ scale, 1.698 for the attractiveness scale value, 1.547 for perspicuity scale, 1.552 for efficiency scale, 1.692 for dependability scale, 1.721 for stimulation scale, and 1.921 for novelty scale. Based on UEQ benchmark scale comparison, the scale of attractiveness, efficiency, dependability, and novelty obtained the â€œgoodâ€ category. Meanwhile, the perspicuity scale obtained the â€œabove averageâ€ category, while the stimulation scale obtained the â€œexcellentâ€ category.